Assessment of Homocysteine, Vitamin B12, and Zinc Levels among Patients with Acute Ischemic Stroke in Northwestern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Stroke has been a global burden, with increasing morbidity and mortality. Several risk factors have been identified, which are the target of preventive strategies, they include hyperhomocysteinemia, hypovitaminosis B12, and low zinc levels. There is paucity of data on the biochemical risk factors in our environment which necessitated this study.Objective:To evaluate the serum levels of homocysteine, vitamin B12, and zinc in patients with acute ischemic stroke in Zaria.Patients and Methods:This is a case-control study conducted over 13 months in ABUTH Zaria. One hundred patients with clinical diagnosis of ischemic stroke diagnosed, confirmed by brain CT-scan and Siriraj stroke score of less than −1, and equal number of apparently healthy age, and sex-matched were recruited. Their fasting serum homocysteine and vitamin B12were measured using enzyme-linked immunosorbent assay, while zinc was measured using direct colorimetric method. Stroke severity was determined using National Institute of Health Stroke Score (NIHSS), patients with NIHSS score of 1–4, 5–15, and 16–42 were classified as mild, moderate, and severe stroke respectively.Results:Mean serum homocysteine for patients was significantly higher than that of controls (P< 0.05) and mean serum zinc and vitamin B12significantly lower compared to that of controls (P< 0.05). There was no association between hyperhomocysteinemia, low vitaminB12, and low zinc concentrations with the severity of stroke using NHISS Score.Conclusion:Elevated serum homocysteine, low vitamin B12, and zinc were found to be significant risk factors associated with ischemic stroke.